Application of Performance Assessment to Improve Problem solving Calculus Student Mastery - Ruslan Ruslan (Universitas Negeri Makassar, 2017)
This research aims to improve student mastery of subject Mathematics Department Calculus II by implementing performance assessment problem solving strategies. This research is categorized as a class action research that uses quantitative and qualitative approaches. The subject of this research are students of mathematics, State University of Makassar, Academic Year 2009/2010 is programmed course calculus II, which numbered 50 students. Data collected by observation, questionnaire distribution, and administration tasks in a matter of solving the problem. Quantitative data were analyzed using SPSS program that includes a percentage, the maximum score, and the average value. And qualitative data were analyzed by first selecting or grouping, and then explain or describe, and finally concluded or give meaning.